2007
DOI: 10.1152/ajpendo.00287.2007
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism is associated with increased circulating bone marrow-derived progenitor cells

Abstract: /CXCR4ϩ cells indicating progenitor cells with the homing receptor CXCR4). Cytokine serum levels (SCF, SDF-1, VEGF, EPO, and G-CSF) were assessed using ELISA. Levels of PTH and thyroid hormone as well as serum electrolytes, renal and liver parameters, and blood count were analyzed. Our data show for the first time a significant increase of circulating BMCs and an upregulation of SDF-1 and VEGF serum levels in patients with PHPT. The number of circulating BMCs returned to control levels measured 16.7 Ϯ 2.3 mo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…Another finding from this SDF-1 and MMP-9 on G-CSF-induced HSPC mobilization F Jin et al research was that the number of immature osteoblasts lining the bone endosteal region (near the HSC niche) also diminished significantly after G-CSF mobilization, which is consistent with the recent publications that bone remodeling also plays role in HSPCs mobilization. [40][41][42][43][44] In conclusion, our study revealed the pivotal role of MMP-9-dependent degradation of SDF-1 in the process of G-CSF-induced HSPCs mobilization. Our group is now evaluating the effect of G-CSF on the osteoblast/osteoclast and the relationship between bone remodeling and the extracellular matrix components (such as SDF-1, MMP-9 and so on) in the HSPCs mobilization.…”
Section: Discussionsupporting
confidence: 54%
“…Another finding from this SDF-1 and MMP-9 on G-CSF-induced HSPC mobilization F Jin et al research was that the number of immature osteoblasts lining the bone endosteal region (near the HSC niche) also diminished significantly after G-CSF mobilization, which is consistent with the recent publications that bone remodeling also plays role in HSPCs mobilization. [40][41][42][43][44] In conclusion, our study revealed the pivotal role of MMP-9-dependent degradation of SDF-1 in the process of G-CSF-induced HSPCs mobilization. Our group is now evaluating the effect of G-CSF on the osteoblast/osteoclast and the relationship between bone remodeling and the extracellular matrix components (such as SDF-1, MMP-9 and so on) in the HSPCs mobilization.…”
Section: Discussionsupporting
confidence: 54%
“…83 In humans, PTH may have similar effects, as both postmenopausal women treated with teriparatide (PTH 1-34) and patients with primary hyperparathyroidism have increased circulating HSPCs. [84][85][86] Whether PTH signaling is a physiologic regulator of the HSC niche is currently not known.…”
Section: Hormonal Signalsmentioning
confidence: 99%
“…Accordingly, patients with primary hyperparathyroidism have an increased number of circulating BM-derived HSPCs in the peripheral blood. 3 Moreover, some PTH regimens increase the population that can later be mobilized by G-CSF, 4 whereas others induce mobilization of progenitor cells from the BM into the peripheral circulation, 5 thus mimicking the effects of G-CSF. Because of these properties, PTH has been investigated as a potential therapeutic agent to enhance HSPC mobilization.…”
Section: Introductionmentioning
confidence: 99%